Study of the relationship of serum Vitamin D and ferritin levels in children with attention deficit hyperactivity disorder - mehta, Ashima; Kalra, B P; Srivastava, Malini (Indian Journal of Child Health, 2022)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent mental health disorders among school-age children in India. Etiopathogenesis is attributed to abnormal dopamine regulation which is influenced by both genetic (genes encodingdopamine-DRD4, DRD5, and DAT1) and environmental factors. Micronutrients such as iron and Vitamin D play imperative roles in neurologic function, neurotransmitter synthesis, and regulation. Aim: The aim of the study was to study the association between Serum Vitamin D and Serum Ferritin levels in children with ADHD. Materials and Methods: This case–control study was conducted in the outpatient department of a tertiary care hospital, from October 2019 to May 2021. Subjects (n=30) included patients with the diagnosis of ADHD (using child behavior checklist and INDT–ADHD). Healthy children of the comparable age group were taken as controls. Statistical analysis was performed using Statistical Package for the Social Sciences software version 22. Results: The mean value of serum ferritin levels in cases was observed to be 32.55±31.97 ng/ml and in controls was 143.43±260.40 ng/ml. The study found a significant difference in the mean value of serum ferritin levels in cases and controls (p?0.024). No significant difference in the mean value of serum Vitamin D in cases and controls (p–0.229) was noted. Conclusions: An association between low levels of serum ferritin and ADHD was seen.